The Influence of Personal Selling on Repurchase Intention Through Customer Satisfaction at Strawberry Kopo Salon - Mey Byilah Arsy Sudrajat; Faizal Fardhani Sigarlaki (Green Publisher Indonesia, 2026)
This study aims to analyze the effect of personal selling on repurchase intention through customer satisfaction as a mediating variable at Salon Strawberry Kopo, Bandung. The background of this research is the fluctuating number of returning customers, which is suspected to be influenced by variations in service quality and the effectiveness of personal interactions between staff and customers. This research employs a quantitative approach using a survey method, involving 130 respondents who are customers of Salon Strawberry Kopo. The analytical techniques used include multiple regression analysis and the Sobel test to examine both direct and indirect effects among variables. The results show that personal selling has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on repurchase intention. Moreover, personal selling also has a direct positive influence on repurchase intention, and customer satisfaction is proven to mediate the relationship between personal selling and repurchase intention. These findings indicate that effective personal selling—through friendly communication, clear information delivery, and service that meets customer needs—plays a crucial role in enhancing satisfaction and encouraging repeat visits. Therefore, improving the quality of personal interactions and maintaining consistent service standards are key strategies for strengthening customer loyalty in the beauty service industry.